Mindfulness-Based Cognitive Therapy (MBCT) in improving quality of life: Case study in Chronic Kidney Disease patients with hemodialysis - Hasanudin, Rini Junita Bakri; Siswandi, Ahmad Gimmy Prathama; Wardhani, Nurul (Psikohumaniora: Jurnal Penelitian Psikologi, 2019)
Chronic Kidney Disease (CKD) not only affects the physical condition but also impacts on psychological conditions, such as feeling down, embarrassed by appearance, feelings of worthlessness, anxiety, to despair which is the cause of decreased quality of life. In improving the quality of life requires a psychological intervention called Mindfulness-Based Cognitive Therapy (MBCT). This study aims to seek the effects of MBCT interventions on improving the quality of life of patients with Chronic Kidney Disease (CKD) with hemodialysis. Research participants were 3 people. This research was a case study research with a mixed method. Data analysis strategy used was a concurrent embedded strategy that compares quantitative and qualitative data. The result showed that MBCT interventions could improve participant’s quality of life. MBCT interventions provide the skills to be aware of clear thoughts, feelings, and events without assessing them so that patients can sort out the things that originate from their thoughts and distinguish them from actual events. This accomplishment of the result can be perceived from the arising of feeling more enjoy life and there is an increase in scores on each aspect of quality of life on the measurement scale used.